assertNotSame( pe1, pe3 );
assertThat(pe1, not( equalTo( pe3 ) ) );
// test eval
EvalCondition ec1 = ( EvalCondition ) rule1.getLhs().getChildren().get( 1 );
EvalExpression ee1 =( EvalExpression) ec1.getEvalExpression();
EvalCondition ec2 = ( EvalCondition ) rule2.getLhs().getChildren().get( 1 );
EvalExpression ee2 =( EvalExpression) ec2.getEvalExpression();
assertNotSame( ee1, ee2 );
assertEquals(ee1, ee2 );
EvalCondition ec3 = ( EvalCondition ) rule3.getLhs().getChildren().get( 1 );
EvalExpression ee3 =( EvalExpression) ec3.getEvalExpression();
assertNotSame( ee1,ee3 );
assertThat(ee1, not( equalTo( ee3 ) ) );
// test consequence
assertNotSame( rule1.getConsequence(), rule2.getConsequence() );